2017
DOI: 10.1021/acs.chemmater.6b05372
|View full text |Cite
|
Sign up to set email alerts
|

Cs1–xRbxPbCl3 and Cs1–xRbxPbBr3 Solid Solutions: Understanding Octahedral Tilting in Lead Halide Perovskites

Abstract: The structures of the lead halide perovskites CsPbCl3 and CsPbBr3 have been determined from X-ray powder diffraction data to be orthorhombic with Pnma space group symmetry. Their structures are distorted from the cubic structure of their hybrid analogs, CH3NH3PbX3 (X = Cl, Br), by tilts of the octahedra (Glazer tilt system a – b + a –). Substitution of the smaller Rb+ for Cs+ increases the octahedral tilting distortion and eventually destabilizes the perovskite structure altogether. To understand this behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
100
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(114 citation statements)
references
References 36 publications
6
100
0
1
Order By: Relevance
“…A single crystal of orthorhombic RbPbBr 3 was first prepared at 310 °C by Cola et al., but it can hardly be synthesized at room temperature . The PXRD patterns in Figure b clearly demonstrate that our obtained NCs adopt an orthorhombic structure, which is consistent with a previous report on the Rb 1− x Cs x PbBr 3 bulk analogue . It is worth noting that the diffraction peaks of the Rb 1− x Cs x PbBr 3 NCs are slightly shifted to lower 2 θ values compared with the standard orthorhombic RbPbBr 3 pattern, and the shift becomes more obvious when increasing the amount of Cs + (Figure c), which can probably be ascribed to the incorporation of the larger Cs + into the lattice.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…A single crystal of orthorhombic RbPbBr 3 was first prepared at 310 °C by Cola et al., but it can hardly be synthesized at room temperature . The PXRD patterns in Figure b clearly demonstrate that our obtained NCs adopt an orthorhombic structure, which is consistent with a previous report on the Rb 1− x Cs x PbBr 3 bulk analogue . It is worth noting that the diffraction peaks of the Rb 1− x Cs x PbBr 3 NCs are slightly shifted to lower 2 θ values compared with the standard orthorhombic RbPbBr 3 pattern, and the shift becomes more obvious when increasing the amount of Cs + (Figure c), which can probably be ascribed to the incorporation of the larger Cs + into the lattice.…”
Section: Resultssupporting
confidence: 88%
“…[18] The PXRD patterns in Figure 2b clearly demonstrate that our obtained NCs adopt an orthorhombic structure, which is consistent with aprevious report on the Rb 1Àx Cs x PbBr 3 bulk analogue. [19] It is worth notingt hat the diffraction peaks of the Rb 1Àx Cs x PbBr 3 NCs are slightly shifted to lower 2q values compared with the standard orthorhombic RbPbBr 3 pattern, and the shiftb ecomes more obviousw hen increasing the amount of Cs + (Figure 2c), which can probablyb ea scribed to the incorporation of the larger Cs + into the lattice.T his result echoeswellt he EDS mapping results in that Cs + is successfully incorporated into the NCs.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The structural characterization (Figure c) showed again a high degree of conversion and crystallinity for the entire series of compounds, with an expected shift to larger angles upon substitution with the smaller cesium cation. The different intensity of the main diffraction peaks between hybrid and fully inorganic perovskites ( y = 1) agrees with the slightly different orientation of the unit cell . The concentration of Cs + in this perovskite series was confirmed by XPS (Figure S7 and Table S1, Supporting Information).…”
supporting
confidence: 69%
“…In contrast to the claimed more stable lattice structure of the Rb‐doped CsPbX 3 NCs, Linaburg et al . performed theoretical simulation and concluded that the Rb‐doped perovskites are likely to form unstable crystal structure . Considering the very small difference in the HRTEM and the XRD results, further investigation on the change to the crystal lattice and the materials stability of Rb‐doped CsPbX 3 NCs are still needed.…”
Section: Metal Doping/alloying Of Perovskite Ncsmentioning
confidence: 99%